Flawless : a pretty little liars novel (the truth won't stay buried forever) - Shepard, Sara, 1977- (London : Atm, 2010)
After their friend who has been missing for more than three years turns up dead, four former best friends continue to receive frightening messages from someone who knows damaging secrets about them.
Keywords: Secrets -- Juvenile Fiction; Conduct of life -- Juvenile Fiction; Friendship -- Fiction; High schools -- Juvenile Fiction; Schools -- Juvenile Fiction; Mystery and detective stories